Artistic Interpretation of Love and Being in Love in Shaybani’s Poetry (Texas Journal of Philology, Culture and History, 2023)
One of the most frequently described themes in Eastern literature is the theme of love. The main part of the divan of Muhammad Shaybanikhan, the Shah and the poet consists of ghazals dedicated to the eternal theme of love. The article shows the interpretation of love in the poet’s work based on some poems on this topic, expressions of emotional states typical of being in love in various passages. Most of the Divan’s ghazals note that Shaybani’s lyrical hero in love is the poet himself, and it is analyzed that his feelings, thoughts, dreams, and sufferings on the path of love were reflected in his work